2015
DOI: 10.1111/crj.12388
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of CTLA4 and CD28 polymorphisms with lung involvement, HRCT findings and pulmonary function tests in Turkish patients with ankylosing spondylitis

Abstract: Our results suggest a possible association of CTLA4 and CD28 variants with AS pulmonary involvement. Furthermore, these results may lead to the development of new therapeutic agents to control more aggressive forms of the disease. However, further studies are needed in larger populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The mice developed abnormal immune activation, multiorgan lymphocyte infiltration, and autoantibodies in a short period of time [42]. CTLA-4 polymorphisms have been significantly associated with autoimmune disorders, namely AS, Graves' disease, and rheumatoid arthritis, in British Caucasian, Irish Caucasian, Iranian, West Algerian, and West Mexican populations but not in a Turkish population [43][44][45][46][47]. It is interesting that the HLA genes and the CTLA-4 proteins were connected through the CD3E protein (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The mice developed abnormal immune activation, multiorgan lymphocyte infiltration, and autoantibodies in a short period of time [42]. CTLA-4 polymorphisms have been significantly associated with autoimmune disorders, namely AS, Graves' disease, and rheumatoid arthritis, in British Caucasian, Irish Caucasian, Iranian, West Algerian, and West Mexican populations but not in a Turkish population [43][44][45][46][47]. It is interesting that the HLA genes and the CTLA-4 proteins were connected through the CD3E protein (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Restrictive lung disease observed in patients with AS is associated with chest cage rigidity and reduced spinal mobility rather than pulmonary parenchymal disease [ 17 ]. Although the consideration that smoking causes interstitial inflammation and pulmonary parenchymal destruction is widely accepted, smoker and nonsmoker AS patients presented similar rates of abnormal HRCT findings [ 9 , 12 , 18 , 19 ]. Turetschek et al have reported the incidence of abnormal HRCT finding as 71% in the nonsmoker AS patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of anti-TNF agents with proven efficacy in the AS patients with resistant axial and peripheral arthritis on the pulmonary involvements has not been widely investigated [ 22 ]. In a recent study, 27 of 89 AS patients (30.3%) received anti-TNF treatment; however, no association was detected between anti-TNF treatment and HRCT findings or PFT results [ 19 ]. Bargagli et al have reported a beneficial effect of infliximab in the treatment of interstitial lung disease associated with rheumatoid arthritis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%